O humor da vida real: a cidade de Sobral (CE) no programa de rádio “Sábado de todas as maneiras” - Costa, Claudiene dos Santos (2019)
In Sobral (CE), the radio program "Saturday in every way" uses the city as inspiration for pictures told with humor by Tupinambá Marques, called Babá. It is intended to identify which aspects of Sobral's memory are presented in the program, from the perspective of Cultural Studies, using Hall's concept of representation (2016). It is observed what kind of scenes and representations of Sobral are highlighted in their fixed pictures, specifically "Watching the life of the famous and almost famous" and "What Sobral has of ‘so-so’". The humorous format of the program reveals traces of popular culture historically linked to the state of Ceará, and when dealing with places, customs and real inhabitants exposes a socially widespread collective memory that generates points of identification with the public. It is perceived that radio favors the presence of humor by combining well with the elements that make up the structure of the radiophonic language: oral language, penetration, mobility, low cost, immediacy, instantaneity, sensoriality and autonomy (MARTINS and SILVA, 2009). To analyze the corpus of the research, it will be used the Critical Discourse Analysis (FAIRCLOUGH, 2001). Transcribed editions of the two specific corpus tables published in the year 2017 will be analyzed in order to observe the interdiscursivity in the creation of the content. In the air since 1997, the radio show exposes in the program a mosaic of stories seized in everyday life. When recording scenes and habits, as in a fabric assembled and remounted on Sobral, we use the idea of the city as palimpsest (PESAVENTO, 2004), collective memory (HALBWACHS, 2006) and representation (HALL, 2016), system by which we firm our senses about the world using language. Analyzing the discourse in a three-dimensional framework, such as text, discursive practice and social practice, we also consider the models in memory (VAN DIJK, 2010), which allow the coherence of discourse for listeners, since they construct a model of the situation, in addition to the representation of the text. In "Watching the life of the famous and almost famous", the trope of irony connects the exceptional and the commonplace in the daily life of the inhabitants, and the attribute of humor indifference, when evil causes laughter and not crying, is what allows the criticism to the city in "What Sobral has of 'so-so'".